Telejornalismo na Cibercultura: A incidência do jornalismo declaratório nas TVs de Campina Grande e sua operacionalidade através do WhatsApp - Gonçalves, Eveline Regina (2018)
The declaratory journalism was already used by the communication vehicles before the cyberculture, but it was after her advent that base news only on the statements of a single source became something recurrent. Our objective with this research is justly know the link between the incidence of the declaratory journalism on the television stations of Campina Grande, on Paraíba, and the use of new technology tools, especially Whatsapp, by journalists. For this, we analyzed two non-probabilistic samples for the convenience of declaratory journalism in each of the three stations of the city. We also conducted semistructured interviews with a producer and the director of journalism vehicles. In this work we discuss the impact of new technologies in journalistic practices, the declaratory journalism before and after the cyberculture, as well as differentiating declaratory from the investigative and collaborative journalism. We proved, in this study, that the facilities for acessing the sources and the declarations in videos or audios sent by it, mainly by Whatsapp, has contributed significantly for the incidence of declaratory in the cyberculture. The content received online with the source's report is being displayed and supporting the news, even if it is a fact of repercussion. This phenomenon may have implications, which we will also discuss, both as regards the quality of the news, and the space of the communication professional in newsrooms.